Pengembangan Metode Sensor Kolorimetri berbasis Nanopartikel Emas untuk Deteksi Dini Penyakit Kanker - Badi'ah, Hanim Istatik; Qomariyah, Ani (Chemistry Department, Universitas Islam Indonesia, 2023)
A gold nanoparticle as colorimetric sensor (AuNp) has been successfully developed for the detection of lactic acid, which is one of the biomarkers of cancer disease. The sensor is based on the presence of a color change in the AuNp solution when it reacts with dihydrogenic acid and is the result of the development of a simpler, faster, and more economical method for early detection and monitoring of cancer. The synthesis method of AuNp was reduced and characterized using UV-Vis and PSA spectrophotometers. Several optimizations were made to obtain AuNP in the best condition as a colorimetric sensor for the detection of lactic acid. The result of AuNp synthesis optimization with HAuCl4 concentration variation was obtained with a smallest size of 17.25 nm and a concentration of 1 mM. The optimum combustion time is 10 minutes, with a result of 17.05 nm. The AuNp colorimetric sensor undergoes a color change from grapefruit to purple when it reacts with fucking acid. The results of the validation of the methods carried out obtained a sensitivity value of 0.2212, a LOD value of 0.21 mM, a LOQ of 0.68 mM, a range of accuracy values of 94.72–106.66%, and % KV of <0.97.